Effect of Check Delay Time Difference on Enumerating Bacteria in Patients with Urinary Tract Infection - Inayah Fitri; Zulfikran Moh Rizki Aziz; Devis Ika Widyawati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Urinary Tract Infection (UTI) is a contamination in the urinary tract is often caused by bacteria. The count of number bacteria must be used in fresh urine. Using postponed urine can cause bacteria in the urine to increase. The purpose of the research was to determine the number of bacteria; severity of UTI based on the number; and the effect of variation in the length of delay in urine examination on the number of bacteria. This research used the purposive sampling method with criteria for patients who did not receive antibiotics treatment. The urine sample was postponed for 1, 2, 3, and 4 hours at room temperature and then scratched in CLED media; after 18 hours of incubation, the number of bacteria is calculating. The results showed based on the One Way ANOVA test known that every postponed variation of examination has an influence on the number of bacteria in the urine, test of post hoc tukey showed that has real different in every postponed variation of examination. The conclusion in this study is that the number of bacteria with time postponed period variation of examination showed that there is increasment increasing Ã¢â°Â¥105 CFU/ml, the level of severity and postponed examination assessment having influence toward influencing the amount number bacteria.